Expectations and perceptions of students for service quality in UTM sports complex - Ooi, Sher Yeen (2010)
Service quality has become a predominant part for all organizations in providing their services as well as in facilities management which aims at improving customer satisfaction and customer retention. Nowadays, customers are becoming less tolerant of bad services. Since the success or failures of sports complex or service is finally determined by customers, it is essential to examine customers’ perceptions and expectations of the quality of the sport services. The aims of this study is to examine the students’ expectations and perceptions towards service quality delivered by Sports Complex of Universiti Teknologi Malaysia (UTM) and to analyze the gap between expectations and perceptions using the gap analysis. The instrument used in this research is questionnaire using a modified SERVQUAL model with Likert Scale questions. A total of 105 sets questionnaires were returned and analyzed from the 120 sets questionnaires randomly distributed to the students who visit and use the sport facilities of UTM Sports Complex. Frequency analysis and mean are used to analyze the first objective while gap analysis is used for the second objective analysis. From the analysis, it is found that the overall expectations service level is considerably high and the perceptions service level towards UTM Sports Complex is moderate. However, service quality delivered by UTM Sports Complex is below the respondents expectations due to the negative service gaps for all 22 service quality statements. Among the five service quality dimensions, "tangible" and "empathy" gained the lowest service gaps. On the contrary, the highest service gap is "assurance" which means that UTM Sports Complex provided the worst in "assurance" services. In conclusion, the top management of the sports complex should pay more attention and put more efforts in improving the service quality of the services provided as service quality has become more and more important.